Global, regional, and national epidemiology of congenital heart disease in children from 1990 to 2021 - Xu, Jiaoli; Li, Qinhong; Deng, Lili; Xiong, Jingxuan; Cheng, Zugen; Ye, Caixia (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCongenital heart disease (CHD) is a leading cause of morbidity and mortality in children globally, with significant variations in outcomes across different regions.ObjectiveTo provide comprehensive estimates of CHD prevalence, mortality, and disability-adjusted life years (DALYs) among children under five years old globally from 1990 to 2021.MethodsUsing data from the Global Burden of Disease (GBD) study, trends in CHD prevalence, mortality, and DALYs were analyzed. Mortality estimates were generated using Cause of Death Ensemble modeling, while prevalence and DALYs were estimated using DisMod-MR 2.1. Systematic literature reviews informed the disability estimates.ResultsIn 2021, the global prevalence of CHD in children under five years was over 4.18 million, reflecting a 3.4% increase since 1990. CHD-associated mortality decreased by 56.2%, and DALYs declined by 55.7% from 1990 to 2021. Low and low-middle Socio-Demographic Index (SDI) regions experienced the highest prevalence and mortality rates. South Asia had the highest number of CHD cases, while Oceania had the highest mortality and DALY rates. India had the highest number of cases, while Afghanistan had the highest mortality and DALY rates.ConclusionsCHD remains a significant global health challenge, with substantial disparities in disease burden across regions. Targeted interventions are needed to improve survival and quality of life, particularly in high-burden areas.